Analisis Biaya Operasional Kendaraan (BOK) Bus Rapid Transit (BRT) Transmusi Kota Palembang dan Program Perhitungan BOK Menggunakan Visual Basic 2008 (Studi Kasus : Koridor 1 Rute Terminal Alang-Alang Lebar – Terminal Ampera) - Zulkifli Adin Ramadhan (Jurnal Teknik Sipil dan Lingkungan, 2014)
In determining the type of vehicle used , PT . SP2J as the transport service developer of BRT Transmusi must select the right vehicle , productive , efficient and economical . In terms of price , maintenance , fuel , tire usage , etc. must be taken into account in order Vehicle Operating Costs (VOC ) can be minimized but still productive . The calculation In the analysis of BOK of BRT Transmusi, on two kinds of vehicles , the bus type of Mercedes Bens OH - 1521 and Hino RK8 - 235 in the corridor's of the terminal of Alang - Alang Lebar to terminal Ampera. BOK of Mercedes Benz's bus brand are smaller even though the price is more expensive than the bus of Hino's brand . BOK's small numbers mean that profits that will be obtained from the company's earnings will be greater . So also by fare box ratio, when BOK figure income divided by company's earnings,and get more points than one means the company gets profit and vice versa . Keywords : BRT , Transmusi , BOK